2018
DOI: 10.1016/j.jad.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Association between irritability and suicide-related outcomes across the life-course. Systematic review of both community and clinical studies

Abstract: Although irritability has been proposed as a promising transdiagnostic factor associated with suicide-related outcomes, the absence of consensus in the definition of irritability (vs anger or reactive/impulsive aggression), the poor methodological quality, and the lack of developmental considerations mitigate the conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 88 publications
1
37
0
Order By: Relevance
“…Similarly, longitudinal studies have also reported an association between the presence of anger at index visit and subsequent suicidal ideation (SI), suicide attempt, or completed suicide (Ducasse et al, 2017; Hogstedt et al, 2018; Start et al, 2019). These findings of association between anger and suicidality are consistent with the previously reported association of constructs related to anger such as irritability (Conner et al, 2004; Jha et al, 2020; Orri, Galera, et al, 2018; Orri, Perret, et al, 2018; Orri et al, 2019; Pickles et al, 2009) and aggression (Fanning et al, 2016; McCloskey & Ammerman, 2018) with suicidality. However, these previous reports have not considered the association between overt behaviors of anger attacks and suicidality.…”
Section: Introductionsupporting
confidence: 88%
“…Similarly, longitudinal studies have also reported an association between the presence of anger at index visit and subsequent suicidal ideation (SI), suicide attempt, or completed suicide (Ducasse et al, 2017; Hogstedt et al, 2018; Start et al, 2019). These findings of association between anger and suicidality are consistent with the previously reported association of constructs related to anger such as irritability (Conner et al, 2004; Jha et al, 2020; Orri, Galera, et al, 2018; Orri, Perret, et al, 2018; Orri et al, 2019; Pickles et al, 2009) and aggression (Fanning et al, 2016; McCloskey & Ammerman, 2018) with suicidality. However, these previous reports have not considered the association between overt behaviors of anger attacks and suicidality.…”
Section: Introductionsupporting
confidence: 88%
“…From a theoretical perspective, the "big build" model characterises escalating behaviours of avoidance, numbing, risk-taking, and anger or aggression as potential transdiagnostic markers of psychological distress (Brownhill, Wilhelm, Barclay, & Schmied, 2005). In the "big build" model, psychological distress is associated with difficulties in self-regulation including irritability and anger (Möller-Leimkühler & Yücel, 2010), which is especially true among younger adult populations (Fava et al, 2010;Massimiliano, Perret, Turecki, & Geoffroy, 2018), as well as problems with goal directed behaviour and motivation (Gillan, Kosinski, Whelan, Phelps, & Daw, 2016), and coping through use of substances (Lai, Cleary, Sitharthan, & Hunt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in adaptive, daily living, and social skills, propensity to fight, rejection from peers and adults, academic failure, lowered quality of life, and self‐esteem (Anastopoulos et al, 2011; Bunford et al, 2018; Lee et al, 2018; Surman et al, 2013) are risk factors for psychiatric problems. Beyond internalizing/externalizing problems, emotional distress combined with the tendency to act impulsively makes individuals more prone to suicidal ideation and attempted suicide (Benarous et al, 2018; Orri, Perret, Turecki, & Geoffroy, 2018). The multifinality of environmental/biological commonalities may also underlie the associations between ADHD, irritability, internalizing, and externalizing problems.…”
Section: Discussionmentioning
confidence: 99%